Outcome of dialysis patients aged seventy years or above – a retrospective analysis (Swiss Medical Weekly, 2014)
OBJECTIVE: Due to increased life expectancy, there is a growing number of older patients with end-stage renal disease (ESRD) requiring renal replacement therapy (RRT). However, there is a lack of data with regard to clinical outcomes of these patients. METHODS: In this single-centre study, we retrospectively analysed two groups of patients on chronic haemodialysis, stratified by age. A group of patients ≥70 years of age (“seniors”; n = 69) was compared with a control group of patients 60 to 69 years of age (“elderly”; n = 39). The major outcomes that we investigated were: patient survival, causes of death, and type and frequency of complications. RESULTS: Kaplan-Meier curves revealed only a trend towards better survival in the elderly (p = 0.06). During the observation time, about half of the patients died: 38/69 in the senior group and 14/39 in the elderly group (p = 0.07). The cause of death was mostly unknown. Both groups were affected equally by complications during haemodialysis therapy (p = 0.62). For the severity of complications, the only significant difference was a higher frequency of complications with outpatient treatment in seniors (p = 0.04). However, there were not more severe complications leading to hospitalisation in seniors (p = 0.64). CONCLUSION: Age is not a good predictor for the outcome of patients of 70 years of age or older with ESRD requiring RRT and thus age alone should never guide us in the decision-making process as to whether to start dialysis or not in these patients.